Phylogenetic Tests of Models of Viral Transmission - Zink, Robert M.; Holck, Kenedi; Morgan, Grant L. (Frontiers in Virology, 2022)
The hunt for the immediate non-human host of SARS-CoV-2 has centered on bats of the genus Rhinolophus. We explored the phylogenetic predictions of two models of viral transmission, the Spillover Model and the Circulation Model and suggest that the Spillover Model can be eliminated. The Circulation Model suggests that viral transmission occurs among susceptible hosts irrespective of their phylogenetic relationships. Susceptibility could be mediated by the ACE2 gene (important for viral docking) and we constructed a phylogeny of this gene for 159 mammal species, finding a phylogenetic pattern consistent with established mammalian relationships. The tree indicates that viral transfer occurs over large evolutionary distances. Although lacking consensus, some studies identify a virus from a particular R. affinis individual (RaTG13) as being most closely related phylogenetically to human SARS-CoV-2. However, other R. affinis harbor viruses that are relatively unrelated to human viruses, and viruses found in this species exhibit sequence differences of up to 20%, suggesting multiple transfers over time. There is little correspondence between viral and host (bat) species limits or phylogenetic relationships. An ACE2 phylogeny for Rhinolophus followed species limits, unlike the pattern in the viral phylogeny indicating that phylogenetic similarity of ACE2 is not a predictor of viral transmission at the bat species level. The Circulation Model could be modified to apply to any individual of any species of Rhinolophus; more individuals and species must be examined.